IMPLEMENTASI SISTEM KOMPUTERISASI AKUNTANSI DENGAN MENGGUNAKAN ACCURATE ONLINE DALAM PENYUSUNAN LAPORAN KEUANGAN SEBAGAI DASAR PENGUKURAN KINERJA KEUANGAN (STUDI KASUS PADA PT ADMIRA) - Prawista, Eluvio Helda; Purnomo, Hari; Akbar, Dharmawan Iqbal (Cahaya Ilmu Bangsa, 2025)
The purpose of this research is to implement an accounting computerization system by using Accurate Online in the preparation of financial statements at PT ADMIRA. The data collection techniques used are interviews and documentation. The data used in this study consist of financial transaction data from September to November 2024. This research is an applied study. The development procedure involves collecting primary and secondary data through interviews and documentation, inputting data into Accurate Online, presenting financial statements, and measuring financial performance by using financial ratio analysis. The results are this study indicate that the preparation of financial statements by applying Accurate Online becomes easier, more accurate, and real-time. The results of financial ratio analysis show that liquidity and solvency ratios indicate good financial performance. For profitability ratios, the condition is good in terms of profit margin; however, the return on assets and equity is in less condition. The activity ratios show good financial performance in receivable turnover but is less favorable in inventory turnover, but there is a need to improve efficiency in utilizing assets.